Shared atypical brain anatomy and intrinsic functional architecture in male youth with autism spectrum disorder and their unaffected brothers. Issue 4 (9th November 2016) - Lin, H.-Y.; Tseng, W.-Y. I.; Lai, M.-C.; Chang, Y.-T.; Gau, S. S.-F.
Abstract : Background: Autism spectrum disorder (ASD) is a highly heritable neurodevelopmental disorder, yet the search for definite genetic etiologies remains elusive. Delineating ASD endophenotypes can boost the statistical power to identify the genetic etiologies and pathophysiology of ASD. We aimed to test for endophenotypes of neuroanatomy and associated intrinsic functional connectivity (iFC) via contrasting male youth with ASD, their unaffected brothers and typically developing (TD) males. Method: The 94 participants (aged 9–19 years) – 20 male youth with ASD, 20 unaffected brothers and 54 TD males – received clinical assessments, and undertook structural and resting-state functional magnetic resonance imaging scans. Voxel-based morphometry was performed to obtain regional gray and white matter volumes. A seed-based approach, with seeds defined by the regions demonstrating atypical neuroanatomy shared by youth with ASD and unaffected brothers, was implemented to derive iFC. General linear models were used to compare brain structures and iFC among the three groups. Assessment of familiality was investigated by permutation tests for variance of the within-family pair difference. Results: We found that atypical gray matter volume in the mid-cingulate cortex was shared between male youth with ASD and their unaffected brothers as compared with TD males. Moreover, reduced iFC between the mid-cingulate cortex and the right inferior frontal gyrus, and increased iFC between the mid-cingulate cortex and bilateral middle occipital gyrus were the shared features of male ASD youth and unaffected brothers. Conclusions: Atypical neuroanatomy and iFC surrounding the mid-cingulate cortex may be a potential endophenotypic marker for ASD in males.